A descriptive epidemiological study of shoulder injury in top level English male volleyball players - Wang, H. K.; Cochrane, T. (International Journal of Sports Medicine, 2001)
The aims of this study were to estimate the prevalence and incidence of shoulder sports injuries, to discover the main shoulder injury, and to survey outcome of treatment or injuries in top level male volleyball athletes. Furthermore, the actions which most commonly cause injuries and the differences of physical characteristics between injured and healthy players were also investigated. Fifty-nine English Volleyball Federation division one athletes were recruited in the 1997/98 and 1998/99 seasons. All subjects completed two different questionnaires; a First recruitment and monthly Follow-up questionnaire throughout the period in question. Twenty-seven of the fifty-nine athletes had a history of shoulder sports injury, with a total of 29 injuries reported. The results of the First recruitment showed that overuse type injuries (19/29) were the main shoulder injuries. Cuff muscle tendinitis was predominant in these injuries (14/29). Furthermore, spiking was the major action during which a shoulder injury (23/29) first occurred. In the follow-up phase the incidences of shoulder chronic injury (or pain), re-injury, and new injury in these twenty-seven players were 3.0, 9.3 and 1.0 injuries/1000 hours of exposure respectively. The mean duration of chronic injury or pain was 2.3 ± 1.3 (± SD) months. The distribution of history of regular training, between injured and healthy subject groups, was significantly different (p = 0.008). This study has identified rotator cuff muscle/tendon injuries or involved lesions as the main shoulder injuries in top level English male volleyball athletes. These injuries result in prolonged shoulder pain symptoms.